2021
DOI: 10.36552/pjns.v25i3.592
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcome of Transpedicular Fixation for Degenerative Spondylolisthesis in Terms of Relief from Backache

Abstract: Objective:  To document the outcome of transpedicular fixation for degenerative spondylolisthesis in terms of relief from backache. Materials & Methods:  This retrospective observational study was conducted in Mardan Medical Complex, Mardan. Static and dynamic spinal X-rays were used to diagnose degenerative spondylolisthesis. This research looked at how patients' pain levels, neurological state, and union improved after surgery. Patients with grade 5 spondylolisthesis, having congenital spinal anoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
2
1
0
Order By: Relevance
“…We found that 90% of the patients had signs of radiological fusion at 6month followup. Similar findings were reported by Ishaq et al 21 and Amir et al 22 The greater degree of fusion is associated with improvement in back pain symptoms and favorable outcomes overall. As we did not perform any interbody fusion, these findings also support the argument that transpedicular fixation alone without interbody fusion can have a higher grade of fusion rates.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…We found that 90% of the patients had signs of radiological fusion at 6month followup. Similar findings were reported by Ishaq et al 21 and Amir et al 22 The greater degree of fusion is associated with improvement in back pain symptoms and favorable outcomes overall. As we did not perform any interbody fusion, these findings also support the argument that transpedicular fixation alone without interbody fusion can have a higher grade of fusion rates.…”
Section: Discussionsupporting
confidence: 86%
“…30 (50%) of the patients and L5-S1 was the most frequent level involved (40%) followed by L4-5 (38.3%). Similar findings were reported by Ishaq et al 21 and Amir et al, 22 however, Singha et al, 23 and Ewiss et al, 24 found L4-5 as the most common level involved (70% and 76% of cases respectively).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation